Sides of interaction of mass-media and state in information society - Ороховська, Л. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article contains the philosophical analysis of the state impact on the mass media and the mass-media influence on behalf of civil society organizations on the state power in the context of Information society.